The Influence of Psychoreligious Therapy to Decrease the Depression Level of Narcotics Prisoners: Living Qur’anic Study in East Kalimantan - Fansuri, Fuad (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
The aimed of this study was to determine the therapy applied. Therapy is a psychological treatment by readinga holy Qur'an as a strength way. This research was a quantitative by using quasi experiment with an unequal control group design. This study compared the results of the experimental group pretest and posttest after being treated with an untreated control group. Depression Level Measurement was applied Beck Depression Inventory (BDI)). The population in this study was Narcotics Prisoners Class III Samarinda. The sample size was 42 people which divided into two groups, namely control group and experimental group. The data in this study were analyzed by Wilcoxon signed-rank test with SPSS assistance program. The results showed that the level of weight loss in the experimental group was from 23.8% to 0%. Weight loss to moderate depression was 2 people, 1 person was in moderate to mild depression 2 people was in mild to normal depression. The resultof normality testshowed a significant level of value as well with p = 0.00 (significance of p <0.05) it was meant that psycho-religious therapy could be used as an alternative measured to reduce the level of depression of inmates.